2013
DOI: 10.1097/fbp.0b013e328364166d
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor stimulant and discriminative stimulus effects of ‘bath salt’ cathinones

Abstract: A number of psychostimulant-like cathinone compounds are being sold as “legal” alternatives to methamphetamine or cocaine. The purpose of these experiments was to determine whether cathinone compounds stimulate motor activity and have discriminative stimulus effects similar to cocaine and/or methamphetamine. 3,4-Methylenedioxypyrovalerone (MDPV), methylone, mephedrone, naphyrone, flephedrone and butylone were tested for locomotor stimulant effects in mice and subsequently for substitution in rats trained to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
167
6
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(205 citation statements)
references
References 16 publications
31
167
6
1
Order By: Relevance
“…In addition to its prolonged effects on blocking DAT-mediated transport, MDPV is also a potent norepinephrine transporter (NET) inhibitor, with greater potency for NET than cocaine or METH (Simmler et al, 2013). Consistent with its potent activity at striatal DATs and NETs, MDPV is also a potent locomotor stimulant (Gatch et al, 2013) and produces conditioned place preference in both rats and mice (Karlsson et al, 2014;King et al, 2015). It also significantly elevates extracellular levels of dopamine in the striatum (Baumann et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition to its prolonged effects on blocking DAT-mediated transport, MDPV is also a potent norepinephrine transporter (NET) inhibitor, with greater potency for NET than cocaine or METH (Simmler et al, 2013). Consistent with its potent activity at striatal DATs and NETs, MDPV is also a potent locomotor stimulant (Gatch et al, 2013) and produces conditioned place preference in both rats and mice (Karlsson et al, 2014;King et al, 2015). It also significantly elevates extracellular levels of dopamine in the striatum (Baumann et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Animal studies (Aarde et al, 2013;Baumann et al, 2012;Bonano et al, 2014;Gatch et al, 2013;Huang et al, 2012;Marusich et al, 2014b;Watterson et al, 2014) and in vitro monoamine transporter assays (Baumann et al, 2012) have shown that MDPV produces typical psychostimulant-like effects, with a mechanism of action that is similar to and, yet, more powerful and longer lasting than cocaine. The biological activity of bath salts, including MDPV, is thought to be largely mediated through their effects on mesostriatal monoaminergic neurotransmission (Cozzi et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although the synthetic cathinone compounds MDPV and mephedrone are less well studied than MA, these compounds can stimulate motor activity in mice (Fantegrossi et al, 2013;Fuwa et al, 2009;Gatch et al, 2013) and rats Baumann et al, 2012Baumann et al, , 2013Huang et al, 2012;Wright et al, 2012) when administered by injection. MDPV appears to be approximately as potent as MA whereas mephedrone is less potent in most prior studies, and thus the relative potencies identified for vapor inhalation in this study (a threshold for effects at 12.5-25 mg/ml for MA and MDPV vs above 100 mg/ml for mephedrone, and significant differences in experiment 3 between mephedrone and the other two drugs) are roughly consistent with prior results using other routes of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Users have reported bath salts producing similar subjective effects as known stimulant drugs of abuse, and the clinical presentation is also similar to cocaine and amphetamine-like drugs (Prosser and Nelson, 2012). Our laboratory has previously demonstrated that a number of synthetic cathinones produce locomotor stimulation in mice and cocaine-and methamphetamine-like discriminative stimulus effects in rats (Gatch et al, 2013(Gatch et al, , 2015. The pharmacodynamic profile of synthetic cathinones is also similar to other psychomotor stimulants, with some derivatives producing amphetamine-like monoaminereleasing properties, and others producing cocaine-like blockade of monoamine uptake (Eshleman et al, 2013;Simmler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%